Editorial: Peer Review for JSE Manuscripts - Charles P. Seeley; Scott W. Greenberger; Morgan McNaughton (Journal of Scholarly Engagement)
Due to the innovative nature of the Journal of Scholarly Engagement (JSE) and given the desire to limit bias in our peer review process, this editorial was written to explain best practices for peer reviewing our unconventional manuscript types. JSE is unique in the field of scholarly publishing in that it is dedicated to documenting and disseminating unconventional forms of scholarly activity (Greenberger & Mandernach, 2018). While most scholarly journals focus on the scholarship of discovery, JSE is focused on the scholarship of application and the scholarship of integration. The scholarship of application explores the application of scholarly or academic knowledge to solve human problems in the context of human situations, while the scholarship of integration brings multiple domains of knowledge together in a way that gives new insight into a problem, issue, or situation. As a result, the story being told in JSE manuscripts should be clear and compelling and the human dimension clearly discussed.